THE USE OF PUMPKIN (Cucurbita moschata) PASTA ON THE DRIED NOODLES PRODUCTION - Novi Safriani; Nida El Husna; Rizka Rizkya (BPFP Faperta UNIB, 2015)
The aim of this study was to utilize pumpkin pasta for partial substitution of wheat flourin the dried noodles production. More over, the effect of drying temperature and time on the characteristics of the dried noodles were investigated. This study was conducted using a completely randomized design factorial consisting of two factors: the drying temperature (50oC, 60oC and 70oC) and the drying time (60, 80 and 100 minutes). The results showed that the best quality of the dried noodles obtained from the treatment combination of the drying temperature and time: 70ºC for 60 minutes. The dried noodles have a moisture content of 9.35%, ash content of 1.53%, protein content of 11%, beta-carotene content of 0.67?g/g, cooking time of 6.62 minutes, the descriptive organoleptic value: color of 1.78 (bright yellow), texture of 2.15 (slightly crumbly), aroma of 2.56 (smell of pumpkin), and the hedonic organoleptic value: flavor of 1,77 (really like), elasticity of 1.98 (really like)